Studies on Genetic Variability and Character Association for Quantitative Traits of Garden Pea (Pisum sativum L.) - Dhangrah, V. K.; Singh, Y. P.; Kaur, Navneet (International Journal of Bio-resource and Stress Management, 2023)
The field experiment was carried out in randomized block design repeating each genotype into 3 blocks at Agriculture Farm of Lovely Professional University, Jalandhar, Punjab, India during rabi season (November–March) of 2015–16. Variability in the breeding population is essential pre-requisite to improve yield, earliness, disease resistance, lodging resistance etc. and the study of correlation and path analysis help in formulating selection indices for yield improvement. Therefore, a study was carried out undertaken to assess the magnitude of genetic variability and character association in twenty four diverse genotypes of garden pea (Pisum sativum L.) based on eleven quantitative characters. Analysis Of Variance (ANOVA) showed the existence of wide variability among the genotypes for all the characters studied. Closer magnitude of genotypic and phenotypic variation also indicated the presence of considerable genetic variability for all characters. High proportion of GCV accompanied with high heritability (in broad sense) and high genetic gain/genetic advance as percentage of mean were recorded for the characters like days to 50% flowering, plant height, harvesting span, dry matter and pod yield. Significant positive genotypic and phenotypic correlations were observed among pod yield and days to 50% flowering, number of pods plant-1 and number of seeds pod-1. These characters also had positive direct effect on pod yield. Hence, it can be concluded that selection is feasible for improvement of the characters studied under investigation.